Meta-analysis of telomere length in 19 713 subjects reveals high heritability, stronger maternal inheritance and a paternal age effect - Broer, Linda; Codd, Veryan; Nyholt, Dale R; Deelen, Joris; Mangino, Massimo; Willemsen, Gonneke; Albrecht, Eva; Amin, Najaf; Beekman, Marian; de Geus, Eco J C; Henders, Anjali; Nelson, Christopher P; et al. (European journal of human genetics : EJHG, 2013)
Telomere length (TL) has been associated with aging and mortality, but individual differences are also influenced by genetic factors, with previous studies reporting heritability estimates ranging from 34 to 82%. Here we investigate the heritability, mode of inheritance and the influence of parental age at birth on TL in six large, independent cohort studies with a total of 19,713 participants. The meta-analysis estimate of TL heritability was 0.70 (95% CI 0.64-0.76) and is based on a pattern of results that is highly similar for twins and other family members. We observed a stronger mother-offspring (r=0.42; P-value=3.60 × 10(-61)) than father-offspring correlation (r=0.33; P-value=7.01 × 10(-5)), and a significant positive association with paternal age at offspring birth (β=0.005; P-value=7.01 × 10(-5)). Interestingly, a significant and quite substantial correlation in TL between spouses (r=0.25; P-value=2.82 × 10(-30)) was seen, which appeared stronger in older spouse pairs (mean age ≥55 years; r=0.31; P-value=4.27 × 10(-23)) than in younger pairs (mean age<55 years; r=0.20; P-value=3.24 × 10(-10)). In summary, we find a high and very consistent heritability estimate for TL, evidence for a maternal inheritance component and a positive association with paternal age.